Branched Multipeptide-combined Adjuvants Potentially Improve the Antitumor Effects on Glioblastoma. Issue 4 (May 2021) - Tran, Thi-Anh-Thuy; Kim, Young-Hee; Jung, Shin; Kim, In-Young; Moon, Kyung-Sub; Jang, Woo-Youl; Lee, Hyun-Ju; Lee, Je-Jung; Jung, Tae-Young
Abstract : The promising immunotherapy effects of a multiple antigenic peptide on glioblastoma (GBM) in a previous study encourage the use of adjuvants to enhance its therapeutic efficacy. Among adjuvants, pan HLA-DR-binding epitope (PADRE) and anti-programmed cell death protein 1 (anti-PD1) have potentially been tested for cancer immunotherapy. Therefore, here we evaluated the ability of PADRE and anti-PD1 to enhance the function of the branched multipeptide against GBM. The potential utility of tumor-associated antigens (ErbB-2 and WT-1) targeting GBM with HLA-A24 was confirmed and a branched multipeptide was constructed from these antigens. The effects of the branched multipeptide and PADRE on immunophenotyping and polarized Th cytokine production in dendritic cells were clarified. The expression of PD1 on T cells and PDL1 on GBM cells was also investigated. The interferon-γ enzyme-linked immunospot and lactate dehydrogenase release assays were performed to determine the function of GBM peptide antigen-specific cytotoxic T cells against GBM cells. Overall, this study showed that both ErbB-2 and WT-1 are potential candidates for branched multipeptide construction. The branched multipeptide and PADRE enhanced the expression of major histocompatibility complex and co-stimulatory molecules and the production of polarized Th1 cytokines in dendritic cells. The increase in the number of interferon-γ + effector T cells was consistent with the increase in the percentage specific lysis of GBM target cells by GBM peptide antigen-specific cytotoxic T cells in the presence of the branched multipeptide, PADRE, and anti-PD1. Our study suggests the combination of branched multipeptide and adjuvants such as PADRE and anti-PD1 can potentially enhance the effects of immunotherapy for GBM treatment. Abstract : Supplemental Digital Content is available in the text.